2005
DOI: 10.1175/mwr2928.1
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Warm-Season Cloud Episodes over East Asia Based on GMS Infrared Brightness Temperature Observations

Abstract: The present study has used the Geostationary Meteorological Satellite (GMS) IR brightness temperature observations to investigate the regional and intraseasonal variability of east Asian warm-season cloud/precipitation episodes (in distance–time space) due to land–sea contrast and latitudinal effects. The data period was May–August 1998–2001, and harmonic analysis was employed as the major tool for analysis. The full domain of study (20°–40°N, 95°–145°E) was divided into northern and southern zones, and into e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 39 publications
11
49
0
Order By: Relevance
“…The third step consists of plains and hills with a mean elevation of less than 500 m. Due to the strong heating effect of the Tibetan Plateau on the regional weather and climate, most studies on the diurnal cycle of precipitation focus on the Tibetan Plateau and the adjacent lee regions with lower terrain. These studies found that the diurnal precipitation peak usually begins over the Tibetan Plateau in the early afternoon and then propagates eastward (Asai et al, 1998;Wang et al, 2004Wang et al, , 2005Fujinami et al, 2005;Yu et al, 2007a;Zhou et al, 2008;Chen et al, 2009a, b;Xu and Zipser 2011;Bao et al, 2011). The plateaus and mountains of the second step also have an important influence on the local diurnal variation of precipitation: because they are much higher than the plains of the third step, the differential solar heating rate between these two steps yields a temperature gradient that can give rise to the MPS circulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third step consists of plains and hills with a mean elevation of less than 500 m. Due to the strong heating effect of the Tibetan Plateau on the regional weather and climate, most studies on the diurnal cycle of precipitation focus on the Tibetan Plateau and the adjacent lee regions with lower terrain. These studies found that the diurnal precipitation peak usually begins over the Tibetan Plateau in the early afternoon and then propagates eastward (Asai et al, 1998;Wang et al, 2004Wang et al, , 2005Fujinami et al, 2005;Yu et al, 2007a;Zhou et al, 2008;Chen et al, 2009a, b;Xu and Zipser 2011;Bao et al, 2011). The plateaus and mountains of the second step also have an important influence on the local diurnal variation of precipitation: because they are much higher than the plains of the third step, the differential solar heating rate between these two steps yields a temperature gradient that can give rise to the MPS circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influences of both the eastern Asia monsoon climate (Tao and Chen, 1987) and complex topography, there are clear seasonal and regional changes in the diurnal cycle of precipitation over eastern Asia. Recent studies have investigated the diurnal variation of precipitation over eastern Asia, including different regions of China (Ohsawa et al, 2001;Wang et al, 2004Wang et al, , 2005Hirose and Nakamura, 2005;Yu et al, 2007a, b;Li et al, 2008;Xu et al, 2009;Huang et al, 2010;He and Zhang, 2010, hereafter referred to as HZ10; Bao et al, 2011;Sun and Zhang, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional and/or seasonal differences of diurnal rainfall patterns not only occur in China [8,[18][19][20], but also exist in other regions of the world, like in Japan [21], island regions in Asia [22,23], the Asian monsoon region [10][11][12], marine continental islands [24,25], northwest South America [26], the United States Great Plains [27], the Andes in South America [28,29], Africa [30] and even the global tropics [31,32]. The convective rainfall maximum late at night or in the early-morning hours over oceans can be explained by radiation-convection interaction theory [33,34].…”
mentioning
confidence: 99%
“…Earlier studies indicated that the solenoidal circulation between the Tibetan Plateau and its leeside lowlands contributes to the extent of the propagating diurnal rainfall over the Yangtze River (Wang et al 2004;Hirose and Nakamura 2005;Wang et al 2005;Huang et al 2010). There, the East Asian jet stream drives the diurnal convection initiated east of the Tibetan Plateau to propagate eastward (Wang et al 2004).…”
Section: Introductionmentioning
confidence: 99%